Supporting adaptive management. Monitoring and evaluation tools and approaches - Pasanen, Tiina; Barnett, Inka (ODI, 2019)
Key messages • This working paper introduces a set of monitoring and evaluation (M&E) tools and approaches, discussing their potential usefulness in supporting adaptive management in development and humanitarian programmes. It emphasises adaptive programmes characterised by complex aspects, such as: (1) they are innovative; (2) they have uncertain pathways for change; or (3) they operate in uncertain or unstable environments. • The majority of these tools have been used in international development for many years. However, adaptive management brings additional challenges for monitoring and evaluating programmes, as they require intentional M&E design from the start that is oriented towards both learning and accountability. • All of the tools and approaches introduced in this paper have potential to support learning and adaptation, although in various ways and at different stages of a programme. Some tools can support strategic planning and diagnosing throughout a programme – especially during design and inception – while others can help analyse causal relationships at specific points in a programme. It is important to tailor the approach used for its intended purpose. However, whether learning and adaptation happens depends also on factors other than the choice of M&E methods. • For some of these approaches a considerable body of evidence already exists but, for many, more practical examples and systematic analysis is needed. In addition to building the evidence base concerned with which approaches are suitable for different types of adaptive programmes and why, it is also important to improve understanding of the enabling environmental conditions necessary for the tools and approaches outlined here to facilitate and strengthen evaluative thinking, evidence-informed decision-making and ongoing programme iteration.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Monitoring, Evaluation and Learning approaches in an adaptive management context - Tsui, Josephine (EPS PEAKS, ODI, 2016)

Outcome mapping: learning brief - Buell, Stephanie; Malallah, Haneen; Mason, Paige (ODI/GLAM, 2020)
Adaptive programmes recognise that certain changes, particularly in behaviours, are complex, non-linear and difficult to measure. This briefing note explores the use of outcome mapping (OM) as a monitoring, evaluation and learning (MEL) approach to track behavioural change and inform adaptation for two programmes: the Pathways to Resilience in Semi-arid Economies (PRISE) research consortium and the Accountability in Tanzania programme (AcT I and AcT II). It discusses the implementation of OM, the ways in which it has enabled adaptation and enabling contexts in order to identify key considerations for MEL specialists and programme managers as they determine whether OM may be the right fit, and how best to use the approach. Key messages OM has a number of different benefits as a MEL approach, including unpacking different uses of information at different levels of programme implementation; helping to develop a common language around progress markers; and going beyond monitoring to inform adaptation throughout implementation. These benefits are important aspects of monitoring, evaluation and learning for adaptive management (MEL4AM), as they provide richer evidence for decision-making at a frequency that could mean real-time learning and change. OM works best when it is embedded throughout the organisation, and as part of programme and organisational culture, rather than tasked to a MEL unit or individual.

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

Doing things differently: Rethinking monitoring and evaluation to understand change - Saferworld (Saferworld, 2016)
Doing things differently: Rethinking monitoring and evaluation to understand change Learning paper Over the past four years, Saferworld has put in place a way of monitoring, evaluating and learning from our work focused on behaviour and relationship change. This paper outlines the process we have gone through to adapt, embed, and embrace an approach inspired by Outcome Mapping and Outcome Harvesting (OH). Key benefits of our monitoring, evaluation and learning approach are: It is simple, but promotes complex discussion and analysis. It allows conflict- and gender-sensitivity to be built into programmes; it promotes analysis of and adaptation to context. Bringing front-line staff and partners into wider conversations with others substantially increases cross-organisational learning.

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry; Patten, Michael Quinn (IDRC Books, 2001)
"Outcome Mapping provides not only a guide to essential evaluation map-making, but also a guide to learning and increased effectiveness, and affirmation that being attentive along the journey is as important as, and critical to, arriving at a destination." - Michael Quinn PattonMore and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. "Outcome Mapping" recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, "Outcome Mapping" debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.

Back to the Drawing Board: How to improve monitoring of outcomes - Dillon, Neil; Sundberg, Amelie (ODI/ALNAP, 2019)

A Guide to Participatory Outcome-Focused Monitoring with Most Significant Change, Outcome Harvesting, and Outcome Mapping - Smith, Richard (CARE, 2023)
Audience This guidance is primarily aimed at development and humanitarian professionals who design or manage monitoring and evaluation processes to support design and implementation of qualitative monitoring using Most Significant Change (MSC), Outcome Harvesting (OH), or Outcome Mapping (OM), which are participatory, outcome-focused qualitative methods. Purpose This guidance is a resource to strengthen qualitative monitoring, specifically addressing commonplace gaps or weakness in the monitoring of complex development and humanitarian projects. Importantly, these gaps include: 1. Lack of evidence about unexpected, as well as expected, changes or outcomes, especially during project implementation. 2. Limited documentation about whether and how a project contributed to change. Such information is vital to learning about what worked and how to build on successes. 3. Limited data to inform the review of theories of change, which limits their function and relevance. Addressing these monitoring gaps has the potential to contribute to more informed and effective adaptive management and learning. This guidance can be used to support the design and implementation of monitoring exercises using MSC, OH, and OM. Specifically, it supports users in choosing among MSC, OH, and OM or blending elements from these approaches. Additionally, it provides practical tips and examples - including expertise gained during the two pilot qualitative monitoring activities conducted in Niger and Bangladesh - as well as other publicly available materials. 1. Relevant CARE guidance and tools include: 1. Qualitative Methods Guidance Note for Monitoring, Evaluation and Learning (MEL) at CARE; 2. Outcome Mapping Manual: Development of a monitoring system for the Right to Food project using Outcome Mapping, CARE Nepal; 3. Tipping Point MEL Methods Brief: Outcome Mapping; 4. The Rolling Profile Tool.

Outcome mapping for health system integration - Tsasis, Peter; Evans, Jenna; Forrest, David; Jones, Richard Keith (Journal of Multidisciplinary Healthcare, 2013)
Health systems around the world are implementing integrated care strategies to improve quality, reduce or maintain costs, and improve the patient experience. Yet few practical tools exist to aid leaders and managers in building the prerequisites to integrated care, namely a shared vision, clear roles and responsibilities, and a common understanding of how the vision will be realized. Outcome mapping may facilitate stakeholder alignment on the vision, roles, and processes of integrated care delivery via participative and focused dialogue among diverse stakeholders on desired outcomes and enabling actions. In this paper, we describe an outcome-mapping exercise we conducted at a Local Health Integration Network in Ontario, Canada, using consensus development conferences. Our preliminary findings suggest that outcome mapping may help stakeholders make sense of a complex system and foster collaborative capital, a resource that can support information sharing, trust, and coordinated change toward integration across organizational and professional boundaries. Drawing from the theoretical perspectives of complex adaptive systems and collaborative capital, we also outline recommendations for future outcome-mapping exercises. In particular, we emphasize the potential for outcome mapping to be used as a tool not only for identifying and linking strategic outcomes and actions, but also for studying the boundaries, gaps, and ties that characterize social networks across the continuum of care.

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.